BACTERIOLOGICAL QUALITY OF DRINKING WATER AT THE REFILL DEPOT OF DRINKING WATER (DAMIU) IN THE WORKING AREA OF THE PARANG HEALTH CENTER, MAGETAN - sunaryo, Sunaryo; Dyah Ayu Kusumaningrum; Hery Koesmantoro; Frida Hendrarinata (Jurnal Higiene Sanitasi, 2022)
Refill Drinking Water Depot (DAMIU) is a business entity that manages drinking water for consumer needs at a price that is relatively cheap and easy to reach for consumers whose economy is middle to lower. If the processed product of the refill drinking water depot does not meet the requirements, it can cause the spread of disease.. The sample population was 24 samples from the inlet and outlet by doing 2 treatments at each Refill Drinking Water Depot. Laboratory examination was carried out with Microbiological Parameters, namely Coliform Bacteria in accordance with the quality standards of the Regulation of the Minister of Health of the Republic of Indonesia No. 492/Menkes/PER/IV/2010. The results obtained by conducting laboratory results that from 6 refill drinking water depots in the work area of the Parang Health Center, Magetan Regency, do not meet the requirements. And from the results of the Observation Sheet, it was found that the Filtration results contained 3 Refillable Drinking Water Depots that met the requirements and the results of Disinfection there were 3 Eligible Refill Drinking Water Depots. From this research, it can be concluded that from the 6 Refill Drinking Water Depots in the Work Area of the Parang Health Center, Magetan Regency, they do not meet the requirements and the results of the observation sheets from the 6 Refill Drinking Water Depots in the Parang Health Center Work Area, Magetan Regency do not meet the requirements due to the filter. Keywords: Refill Drinking Water Depot, Filtration and Disinfection